STATE OF NONSPECIFIC RESISTANCE IN GIRLS AFTER THE ABORTION - M. N. Svistelnik; Y. I. Ishpakhtin; E. A. Scherbavskaya; A. V. Shirkovets (Acta Biomedica Scientifica)
During one year after the abortion complications such as purulo-septic diseases, disorders of menstrual cycle develop in teenage girls. The basis for these complications are the changes in state of immunological reactivity. The state of local protection, system, varies greatly after the abortion than in the control group. Individual analysis of immunological parameters allows to evaluate them, more accurately and enhances the diagnosis of local defense. Teenage girls after the abortion had. prevalence of increased rates. On the basis of limits of studied, indices their reference values and. criteria for diagnosis of local defense system, with, a 95% probability of accuracy are designed.